RELATIONSHIP OF PHYSICAL ACTIVITY AND VALUE-DEONTOLOGICAL COMPETENCE OF IT SPECIALIST - Pelekh, Y. V.; Shlikhta, G. O.; Grygus, I. M. (Rehabilitation and Recreation, 2024)
The article highlights the analysis of the state of value-deontological competences of IT specialists with work experience of 5 years or more, as well as physical activity. The goal is to show the connection between the level of physical activity, sports regime and the level of value-deontological competencies of IT specialists. Research materials and methods. Analysis of Internet search databases (Scopus, Web of Science, ResearchGate, Google Scholar), a systematic review of materials and studies on the impact of physical activity on various aspects of life was carried out. The following empirical methods were used to conduct the experiment: survey, interview and experiment. The following methods of mathematical statistics are used to process the results: correlation analysis, proving the statistical significance of the results, SPSSv25.0 toolkit. Research results. The results of the study showed a positive relationship between the level of physical activity and value-deontological competencies of IT specialists. Respondents who had a high level of physical activity also showed a higher level of responsibility and ethics in work, which in turn indicates that supporting a sports regime can contribute to the formation and improvement of value-deontological principles among IT specialists. At the same time, interviewed IT professionals with a high level of physical activity showed greater self-discipline and concentration in making ethical decisions. Conclusions. Such conclusions of the empirical study indicate that regular physical activity can contribute to the development of such key competencies as self-control and the ability to analyze situations and emphasize the importance of supporting physical activity among IT professionals to increase the level of value-deontological competencies, which in turn will contribute to successful professional activity, and therefore the quality of services provided in the field of IT.